SUSTAINABLE SPRINGS MANAGEMENT FOR WATER SECURITY OF THE NAGARI PANTI TIMUR COMMUNITY COMMUNITY, PANTI DISTRICT, PASAMAN DISTRICT - Helny Lalan; Hardy Wijaya; Elviyanti, Elviyanti; Robby hotter; Julita Andrini; hafiz Maulana; Randi Maulana; Muhammad afdal (Journal of Community Service, 2024)
Nagari Panti Timur, Panti District, Pasaman Regency, has water resources in the form of natural springs which are the main source of the community's clean water needs. However, various problems such as deforestation, lack of awareness of water conservation, and limited water distribution infrastructure threaten the availability and quality of these water resources. This Community Service activity aims to provide education, training and technical solutions in sustainable spring management. Methods for implementing this activity include identifying problems through surveys and interviews, educating the public regarding water conservation, as well as implementing technical solutions such as building infiltration wells, simple filtration systems, reforesting catchment areas, and building spring water reservoirs. Apart from that, monitoring and evaluation is carried out to ensure program sustainability. The results of the activity showed that the community gained an increased understanding of the importance of water conservation and skills in managing water resources. The infrastructure that has been built is expected to increase the availability and distribution of clean water. The sustainability of this program requires active support from various parties so that the benefits continue to be felt by the community.